Inovasi Pembelajaran Fikih Bagi Generasi Alpha: Implementasi Model PAKEMATIK dan Media Audio Visual - Fitri Alrasi; Azwar; Andryadi; Weti Susanti (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The purpose of this study is to examine the relevance of using the PAKEMATIC model and AudioVisual media for Islamic jurisprudence learning for the alpha generation. The research method uses a literature study. The results of the study showed that the application of PAKEMATIC in Islamic jurisprudence learning not only improves the quality of learning but also encourages students to understand and apply Islamic values ​​​​relevantly in everyday life. With an active, creative, effective, fun, and technology-based approach, Islamic jurisprudence learning can be more interesting and meaningful for today's digital generation. The use of audio visual media in Islamic jurisprudence learning provides a great opportunity to increase student understanding, interest, and participation. With the combination of audio and visuals, abstract or procedural Islamic jurisprudence concepts can be explained more easily and interestingly. Educators must design the right strategy to utilize this media effectively, so that learning objectives can be achieved optimally. It is hoped that by using the PAKEMATIC model and audio visual media in Islamic jurisprudence learning for the alpha generation, it can accelerate the understanding of the material presented.